Advanced concepts in fault tree modularization - Camarinopoulos, Leonidas; Yllera, Javier (Nuclear engineering and design, 1986)
In the present paper a new modular decomposition concept is presented, which unifies and generalizes those known. This is done by characterizing a module by a set of modular functions on a modular set of components, rather than by a single modular function. This extension of the module concept leads to a more flexible and efficient modular decomposition, thus providing a powerful method to compute reliability parameters of very large fault trees containing many repeated events, which considerably impede modularization by existing procedures. However, the efficiency of the method depends on an appropriate selection of the modules and on the methods available for evaluating modular functions. These two subjects are treated in detail in this work, which in addition proposes an algorithm for modular evaluation of fault trees. The implementation of this algorithm in the computer code TREEMOD and its application to the evaluation of some examples serve to illustrate the advantages of the method.